2000
DOI: 10.2527/2000.78102497x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ruminally protected choline and dietary fat on performance and blood metabolites of finishing heifers.

Abstract: A 120-d finishing study utilizing 318 heifers (342 kg initial BW) was conducted to examine effects of ruminally protected choline (RPC) in diets containing graded concentrations of tallow. Heifers were blocked according to previous nutrition (full-fed or limit-fed) and allotted to 24 pens containing 11 to 15 heifers. Two pens, one within each block, were assigned to each of 12 factorially arranged treatments including dietary tallow (0, 2, or 4%) and supplemental RPC (0, 20, 40, or 60 g of product daily, estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 29 publications
2
10
2
4
Order By: Relevance
“…Puchala et al (1998) similarly observed no responses to choline when infused via the duodenum of calves. These observations are in contrast to those of Bindel et al (2000) and Drouillard et al (1998), who demonstrated that finishing cattle respond positively to supplementation of ruminally protected choline. One function of choline is methyl group donation via betaine.…”
Section: Methodscontrasting
confidence: 83%
“…Puchala et al (1998) similarly observed no responses to choline when infused via the duodenum of calves. These observations are in contrast to those of Bindel et al (2000) and Drouillard et al (1998), who demonstrated that finishing cattle respond positively to supplementation of ruminally protected choline. One function of choline is methyl group donation via betaine.…”
Section: Methodscontrasting
confidence: 83%
“…Dietary fat stimulates intestinal cholesterol synthesis (Nestel et al, 1978) to meet the growing demand of absorption and transport of fat which may explain our results. Bindel et al (2000), Febel et al (2002) and Khorasani and Kennelly (1998) also reported increased cholesterol and free fatty acid level in serum by fat supplementation.…”
Section: Resultsmentioning
confidence: 84%
“…This lack of agreement among laboratories may reflect different sampling times in relation to feeding, fewer samples collected than collected in the current experiment, and different amounts of fat intake. Bindel et al (2000) reported increased concentrations of plasma TAG in feedlot heifers fed 5 or 10 g/d of RPC ions compared with heifers fed 0 g/d of RPC ion when tallow was absent from the diet. Tallow supplementation dramatically increased concentrations of plasma TAG and RPC supplementation did not increase TAG concentrations further.…”
Section: Fat Loadingmentioning
confidence: 96%